2004
DOI: 10.1007/s11096-004-0558-3
|View full text |Cite
|
Sign up to set email alerts
|

The quality of drugs in private pharmacies in Lao PDR: a repeat study in 1997 and 1999

Abstract: Drug quality was improved. However, the prevalence of substandard drugs was still unacceptably high, which may result in adverse clinical effect or treatment failure for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 16 publications
3
73
0
Order By: Relevance
“…A large randomized, blinded study with random and adequate sampling is needed to accurately determine the epidemiology of lowquality antimicrobials. Only a limited number of studies had adequate methodology and random sampling (2,15,59), whereas sampling bias, inappropriate storage conditions (38), and instability of certain antibiotics (28) limited the value of the reported data in most studies. Other reports were restricted or not published (59).…”
Section: Determination Of the Epidemiology Of Low-quality Antimicrobimentioning
confidence: 99%
See 3 more Smart Citations
“…A large randomized, blinded study with random and adequate sampling is needed to accurately determine the epidemiology of lowquality antimicrobials. Only a limited number of studies had adequate methodology and random sampling (2,15,59), whereas sampling bias, inappropriate storage conditions (38), and instability of certain antibiotics (28) limited the value of the reported data in most studies. Other reports were restricted or not published (59).…”
Section: Determination Of the Epidemiology Of Low-quality Antimicrobimentioning
confidence: 99%
“…(15), the prevalence of substandard/counterfeit antimicrobials varied from 10% to more than 50% in some studies (2,7,38,79,80), whereas in another report it was 28.5% (range, 11 to 48%) and was similar in developing countries (22 to 38%). In the latter review, out of a total of 44 identified studies, only 15 studies were included in the analysis based on quality criteria (59), four used random sampling methods (7,28,81,82), and only one included sample size estimates (81). Packaging analysis of the collected samples was performed in only two studies from Southeast Asia (40,58).…”
Section: Counterfeit Drugs Have Been Reported Worldwidementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, substandard narrow-spectrum antibiotics may make prescriber think that the antibiotics are not effective, thus unnecessarily prescribe a newer broad-spectrum antibiotics as their first-line treatment for many infections [18]. It has been reported that in Laos, ampicillin contained 3-32% and tetracycline contained 8-14% than expected [19], while in Myanmar more than 20 products of antibiotics contain only 13-48% than expected [20]. Similar problem also has been reported in other developing countries [21,22].…”
mentioning
confidence: 99%